Socio-Political instability in Baluchistan: A growing barrier to polio eradication - Umair Wajid; Muhammad Hassan Ahsan; Haris Muhammad Anwer (Journal of the Pakistan Medical Association, 2026)
Respected Madam, Pakistan’s polio eradication program, led by the Expanded Program on Immunization (EPI) under the Ministry of National Health Services, implements mass and routine immunization strategies in collaboration with WHO, UNICEF, and global health partners.[1] National and Sub-National Immunization Days are conducted alongside routine immunization to increase coverage, while surveillance measures, such as environmental sampling and epidemiological monitoring, help detect outbreaks early, ensuring prompt response and control. Additionally, community engagement initiatives address vaccine hesitancy and enhance immunization uptake, contributing to Pakistan’s ongoing polio eradication efforts. Polio vaccination in Pakistan faces significant challenges, including security threats, vaccine hesitancy, misinformation, and logistical barriers. Geographic inaccessibility and mistrust further hinder immunization progress. Recently, Pakistan’s polio eradication efforts face a surge in cases in Baluchistan, worsening existing challenges. In 2024, 74 polio cases were reported nationwide, with 27 from Baluchistan, including 7 from district Killa Abdullah, highlighting the region’s vulnerability.[2] New socio-political unrest, protests, and security threats in the region have further disrupted vaccination campaigns, limiting access to high-risk populations and compounding existing barriers.[3] Addressing the surge in polio cases in Baluchistan amid security challenges and socio-political unrest requires a multi-faceted, adaptive approach. Ensuring the security of vaccination teams through coordination with local authorities is essential, while integrating polio vaccination into routine healthcare services ensures continuity during disruptions. Engaging local leaders and influencers can help reduce vaccine hesitancy and counter misinformation, fostering trust within communities. A holistic, security-focused, and community-driven strategy by the government is essential for eradicating polio in Baluchistan.